PERAN BADAN PENANGGULANGAN BENCANA DAERAH DAN PEMADAM KEBAKARAN (BPBDPK) KOTA PADANG DALAM PENANGGULANGAN KEBAKARAN - Rifqi Ikhsan Pratama; Darmini Roza (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
The problems in this research are: First , how are the roles of Regional Disaster Management Agency and Fire Department (BPBDPK) of Padang City in fire prevention in Padang City ? Second, what are the obstacles faced by BPBDPK Padang in fire prevention in Padang City? Third, what are the efforts made by BPBDPK in the fire prevention in Padang City?The approach method used in this research is the normative juridical approach as the main approach and supported by the empirical juridical approach. Sources of data used are secondary data and primary data. Data collection techniques used were field studies through interviews for primary data and library studies to find secondary data. Then the data is analyzed qualitatively and described in the form of analytical descriptive.From the research results obtained conclusion; Firstly , BPBDPK Padang has a strategic role because BPBDK Padang is an institution that is given authority and responsibility to handle fire problem in Padang City which is manifested in the role of organizer, role as coordinator, supervisor role, role as facilitator and role as a planner. All these roles are well underway and have been fully implemented in accordance with the main tasks and functions owned by BPBDPK Padang. Secondly, in the fire prevention in Padang City , BPBDPK of Padang City faces a number of obstacles such as: (a) The lack of water source in Padang city to support the fire handling process in Padang City; (b) Many obstacles to fire fleet units during the trip to the fire scene; (c) Lack of public awareness of the existence and working system of fire-fighters; and (d) Non-fulfillment of Fire Management Area (WMK) in every sub-district in Padang City. Third, natural d fire prevention in the city of Padang, the efforts made by BPBDPK Padang is: (a) education and training of personnel BPBDPK Padang; (b) Increasing community participation; (c) Improving institutional coordination ; and (d) Simulation of fire response time.